THE YIELD OF ANJASMORO CULTIVARS SOYBEAN [Glycine max (L.) Merrill] WITH COMPOST TREATMENT FROM TOBACCO OR SOURSOP LEAVES AND ITS WEED CONDITIONS - Sumarmi, Sumarmi; Triyono, Kharis; Sholihah, Efi Nikmatu (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2023)
One of the important problems in soybean production is the weed growth. This study was conducted to observe the growth of weeds in the growth of soybean plants that are given compost. Anjasmoro soybean varieties were planted in Surakarta, on April 14, 2020. There are four types of treatment, namely given compost fertilizer made from tobacco leaves, soursop leaves, a mixture of tobacco leaves and soursop, and without fertilizer. Weeds were allowed to grow together with soybeans in 15 polybags, per treatment. Observation and identification of weeds were carried out twice, 4 weeks after planting and at harvest time. The results found 9 kinds of weeds consisting of 5 species of Monocots and 4 types of Dicotiles. The total wet weight of weeds was every treatment: 1,539 grams, while the wet weight of the soybean crop at harvest was 858.4 grams. Wet weed weight in the control treatment was 284,8 grams. The wet weight of weeds in soybean plants was the largest mixture fertilizer treatment that is 514,8 grams. The number of pods ranges from 17 to 26. The sum of seeds per soybean plant in giving mixed compost is at most 98 grains. Mixed fertilizer treatment can increase the yield of Anjasmoro soybean, although weed growth up.